2018
DOI: 10.1007/978-3-030-00937-3_30
|View full text |Cite
|
Sign up to set email alerts
|

Automated Performance Assessment in Transoesophageal Echocardiography with Convolutional Neural Networks

Abstract: Transoesophageal echocardiography (TEE) is a valuable diagnostic and monitoring imaging modality. Proper image acquisition is essential for diagnosis, yet current assessment techniques are solely based on manual expert review. This paper presents a supervised deep learning framework for automatically evaluating and grading the quality of TEE images. To obtain the necessary dataset, 38 participants of varied experience performed TEE exams with a high-fidelity virtual reality (VR) platform. Two Convolutional Neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…AI-guided visualization and automated skill assessments built into our system may accelerate clinicians’ transition from novice to expert. Success stories in TEE training will be exponential if appropriate 3D visualization-based training on an integrated platform can be established [ 111 , 112 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AI-guided visualization and automated skill assessments built into our system may accelerate clinicians’ transition from novice to expert. Success stories in TEE training will be exponential if appropriate 3D visualization-based training on an integrated platform can be established [ 111 , 112 ].…”
Section: Discussionmentioning
confidence: 99%
“…This AI-driven approach also holds promise in aiding novice TEE trainees. [ 112 ] 2018 3D-printing, 3D-VR headset, and desktop delivery This study assessed the efficiency of three distinct 3D techniques for preoperative planning and management. The results revealed that clinicians expressed a willingness to incorporate 3D virtual reality.…”
Section: Table A1mentioning
confidence: 99%